2010
DOI: 10.1186/1471-2164-11-569
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide characterization of simple sequence repeats in cucumber (Cucumis sativus L.)

Abstract: BackgroundCucumber, Cucumis sativus L. is an important vegetable crop worldwide. Until very recently, cucumber genetic and genomic resources, especially molecular markers, have been very limited, impeding progress of cucumber breeding efforts. Microsatellites are short tandemly repeated DNA sequences, which are frequently favored as genetic markers due to their high level of polymorphism and codominant inheritance. Data from previously characterized genomes has shown that these repeats vary in frequency, motif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

47
262
5

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 318 publications
(314 citation statements)
references
References 77 publications
47
262
5
Order By: Relevance
“…The numbers of polymorphisms in the compound EST-SSRs were slightly lower than those in the noncompound EST-SSRs (Table 2). These results are consistent with what has previously been reported: that SSR polymorphisms are closely associated with their forms, motif sizes, repeat numbers, and repeat lengths (Temnykh et al, 2001;Buschiazzo and Gemmell, 2006;Yi et al, 2006;Kelkar et al, 2008;Cavagnaro et al, 2010). …”
Section: Methods and Resultssupporting
confidence: 82%
“…The numbers of polymorphisms in the compound EST-SSRs were slightly lower than those in the noncompound EST-SSRs (Table 2). These results are consistent with what has previously been reported: that SSR polymorphisms are closely associated with their forms, motif sizes, repeat numbers, and repeat lengths (Temnykh et al, 2001;Buschiazzo and Gemmell, 2006;Yi et al, 2006;Kelkar et al, 2008;Cavagnaro et al, 2010). …”
Section: Methods and Resultssupporting
confidence: 82%
“…As our df Degree of freedom, SS Sum of squares, MS Mean Square selection of SSR loci was biased towards di-nucleotides, so it was difficult to correlate the polymorphism with the repeat type of SSR loci. SSR polymorphism has, however, sometimes been correlated with repeat length, and dinucleotide AT-rich repeats have been found more polymorphic than other kinds of repeats by some groups like Cavagnaro et al (2010) and Kantartzi et al (2009). Guo et al (2007) found the polymorphic rate of tetranucleotide and dinucleotide repeat types slightly higher than that of trinucleotide repeat types.…”
Section: Microsatellite Diversitymentioning
confidence: 99%
“…Totally, 14 MLO genes were obtained from the cucumber 9930 genome and were named CsMLO01 through CsMLO14 (Table 1). Recently, a cucumber gynoecious inbred line (Gy14) was also sequenced de novo using an appropriate mixture of random shotgun and paired-end shotgun reads sequenced with 454-XLR technology (Cavagnaro et al, 2010). The extent of variability between cucumber GY14 and 9930 for MLO genes was assessed using known MLO-like genes from 9930 and other plants in a BLAST search against the GY14 genome sequences (http://genome.…”
Section: Identification Of Csmlo Gene Family Membersmentioning
confidence: 99%